Methods of teaching the native language in an integrated way of natural sciences - Shakarova Lobar; Lecturer Berdiyev Aliboy; Lecturer Baymatov Abduaziz (Zien Journals, 2022)
This article advises students on how to develop their interest in nature, develop logical thinking skills, and develop reasoning skills by combining their native language course with science.
Keywords: lesson; mother tongue; nature; teacher